2014
DOI: 10.1117/1.oe.53.1.013109
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and modeling of laser range profiling and imaging of small surface vessels

Abstract: The detection and classification of small surface targets at long ranges is a growing need for naval security. Simulations of a laser radar at 1.5 μm aimed for search, detect, and recognition of small maritime targets will be discussed. The data for the laser radar system will be based on present and realistic future technology. The simulated data generate signal waveforms for every pixel in the sensor field-of-view. From these we can also generate two-dimensional (2-D) and three-dimensional (3-D) range and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A comprehensive and coherent risk assessment is not expectable until common modeling with verified data is established. Recent progress in modelling of environmental scenes is tremendous, for example as shown in [30]. However consumption of resources of such simulations is high, a lot of data has to be gathered, fitted to the models and processed.…”
Section: Further Studies Requirements and Possible Solutionsmentioning
confidence: 99%
“…A comprehensive and coherent risk assessment is not expectable until common modeling with verified data is established. Recent progress in modelling of environmental scenes is tremendous, for example as shown in [30]. However consumption of resources of such simulations is high, a lot of data has to be gathered, fitted to the models and processed.…”
Section: Further Studies Requirements and Possible Solutionsmentioning
confidence: 99%
“…To the best of our knowledge, previous studies have shown that the ELPP is mainly affected by the response of detectors [12], targets shape [13] and atmosphere, etc [14]. Although previous studies have presented relative results on the ELPP affected by targets [5,15,16], the results are based on the assumption of neglecting effect from atmospheric turbulence. Meanwhile, the theoretical model of the ELPP of a target with arbitrary shape has not been studied under the condition of combinations of target and atmospheric turbulence.…”
Section: Introductionmentioning
confidence: 96%
“…With the fast development of pulse laser, many detecting sensors such as ranging sensors [1,2] and three-dimensional (3D) sensors [3,4] have been studied and developed. Moreover, target recognition based on pulse laser has attracted much attention these years due to its ability to acquire echo pulse with high accuracy and efficiency [5,6]. Therefore, it has been widely used in applications including remote sensing [7], navigation [8] and tracking [9], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical range-based sensors such as stereo vision [1][2][3][4] and scanning light detection and ranging (LIDAR), [5][6][7] have commonly been used in target surface acquiring. Optical range-based sensors such as stereo vision [1][2][3][4] and scanning light detection and ranging (LIDAR), [5][6][7] have commonly been used in target surface acquiring.…”
Section: Introductionmentioning
confidence: 99%